A possible occurrence of twinning in wild muskoxen, West Greenland - Elsner, Wendy (Rangifer, 1994)
Two cows, both at least four years of age, were observed with what appeared to be two sets of twins, near Ammolortoq Lake, approximately 25 km southeast of Kangerlussuaq in West Greenland. There were few other muskoxen in the atea at the time. The calves in each pair were the same size and one pair was larger than the other.